DAMPAK RELAKSASI PPh UMKM DI MASA PANDEMI COVID-19 - Susi Dwi Mulyani; Victor Siagian; Henik Hari Astuti Astuti; Aris Riantori Faisal; Giawan Nur Fitria (JURNAL ABDIKARYASAKTI, 2021)
Community Service Activities are one part of the Tri Dharma of Higher Education which is carried out as a form of direct contribution of academics in this case the Faculty of Economics and Business, Trisakti University (FEB Usakti) to the community. The purpose of this activity is to provide training on: i) review of tax incentives for MSME actors provided by the Indonesian government in accordance with the Regulation of the Minister of Finance; ii) tax administration application training to obtain tax incentives; and iii) training on reporting procedures for tax incentives that have been received by MSME actors. On this occasion the FEB Usakti team had the opportunity to collaborate with PD Pasar Jaya, market unit of Santa as a partner, to socialize tax incentives for Micro, Small and Medium Enterprises (MSMEs) during the COVID-19 pandemic. This pandemic has caused a decline in the performance of MSMEs which then resulted in a very significant decrease in MSME income. The Indonesian government through the Ministry of Finance made a relaxation policy in the form of tax incentives for taxpayers affected by the 2019 corona virus disease pandemic. The Indonesian Ministry of Finance then issued a Minister of Finance Regulation number 44/pmk.03/2020, the last with PMK number 82/PMK.03/2021, one of which provides relaxation for PPh payments to MSME actors. Many MSME business actors do not know about this tax facility. For MSME actors who are subject to Final Income Tax based on Government Regulation Number 23 of 2018, due to the impact of the COVID-19 pandemic, the income tax is borne by the government. The PPh period borne by the government starts in April 2020 and has been extended several times. When the training was held, which was February 24, 2021, the government-paid PPh facilities were still valid and extended until December 31, 2021. This training can increase the understanding of MSME actors towards the tax facilities provided by the government, so that they will take advantage of this facility.